Personality and Creativity: A Study in Spanish-Speaking Children - Gabriela Krumm; Viviana Lemos; María Cristina Richaud (International Journal of Psychological Research, 2018)
This work aimed at studying the relationship between personality from the Big Five Personality model and creativity through different techniques (i.e., a paper and pencil task, and scales) and informants (i.e., the child and parents). We evaluated a sample of 359 Spanish-speaking school children of both genders, aged 9 to 13 years. Personality was assessed with the Argentine Questionnaire of children’s Personality (CAPI). Creativity was evaluated using the following instruments: The Torrance Test of Creative Thinking-Figural Form B; and the Creative Personality Scale (EPC). Pearson correlations and multiple linear regressions consistently showed that Neuroticism related negatively to creativity while competence has a positive relation. The results suggested that more creative children presented less vulnerability, irritability and psychological distress, eventually becoming more independent, competent and emotionally self-regulated in coping with environmental demands.